Persistence and transformation in economic development - Dell, Melissa (Indian economic review, 2021)
Much work in economic history has been done to study patterns of development in the USA and Europe. However, insights from other areas and regions are also required to better inform policy today that helps elucidate how policy interacts with the broader historical and institutional context and how the effects of these policies unfold over time. In this light, the paper focuses on illustrations from previous works of the author on extractive colonial institutions and their persistent effects on development paths later on. The first example is of the Peruvian mining mita. Here, the natives of Peru were forced by the Spanish to work in silver mines. The study focusses on the persistence of differential land tenures and public goods provision. The second example, a joint work with Ben Olken, considers Java’s cultivation system in the 19th century, where the Javanese were forced to produce sugar that was sold in the world market by the Dutch. It shows that the sugar factory areas of the 19th century are more industrialized today. They are richer with better infrastructure and education levels as compared to the nearby counterfactual locations.